Epitaxial strain and thickness dependent structural, electrical and magnetic properties of La0.67Sr0.33MnO3 films. (30th June 2020) - Chaluvadi, Sandeep Kumar; Ajejas, Fernando; Orgiani, Pasquale; Lebargy, Sylvain; Minj, Albert; Flament, Stephane; Camarero, Julio; Perna, Paolo; Méchin, Laurence
Abstract: The crystal structural quality and the strain induced by the substrate strictly impose the magnetic and transport properties of La0.67 Sr0.33 MnO3 (LSMO) films. In particular, the magnetic anisotropy (MA) of epitaxial LSMO can be finely tuned by varying its thickness and by choosing single crystal substrates with a suitable lattice mismatch with the film. Here, we have deposited LSMO films with thicknesses in the 12–50 nm range by pulsed laser deposition on different single crystal substrates inducing either compressive or tensile in-plane strain on the manganites. The epitaxial quality of films was quantified by ω-scans around a (002) peak with full-width half-maximum values as low as 0.08° for films on the nearly matched NGO (110) substrate to 1.4° films on the high mismatched MgO (001) substrate. As the epitaxial strain in a thin-film increases, a significant reduction in the metal-insulation transition temperature (Tp ) was observed. The magnetic properties of the films probed by Kerr magnetometry show that the symmetry of the room temperature MA varies significantly as a function of both strain and thickness. Specifically, we observed pure uniaxial MA on NGO (110) and pure biaxial MA on STO buffered MgO (001), whereas a spin reorientation from uniaxial in-plane to out-of-plane on LSAT (001) and uniaxial to nearly isotropic in-plane on STO (001) substrate as the film thickness is increased. We provide an efficient tool to tune the MA according to the specific spintronic application targeted.